Dimensões da competência em informação: análise dos registros na fala.br - Pereira, Welington Batista (2023)
Currently, scholars and society as a whole experience the abundance of technologies and information, which has highlighted the importance of information literacy. This literacy refers to the ability to access, evaluate, interpret and use information effectively. Since the digital revolution, there have been significant changes in the skills required in the professional field and in social relationships. Information professionals have been leading discussions on the topic for more than five decades, emphasizing the importance of making people literate beyond reading and writing. In Brazil, researchers and information professionals have been active in information literacy studies, expressed in manifestos and declarations. The present study evaluates the dimensions of information literacy presented by Vitorino and Piantola (2011) in relation to the practice of registering requests for information, as a means of accessing information in public transparency, through the Fala.BR Platform. The research was based on a bibliographical survey and, later, on documentary research that provided raw data from requesters of information and records of requests for information made on the Fala.BR Platform, the basis for applying the comparative procedure method. The amount of these records of requests for information represents the set of elements of the research universe. With these tabulated elements, crossings and categorizations were carried out in alignments determined by the proposed objectives. The results obtained showed the importance of encouraging the promotion of information literacy and access to public information for citizenship, from the public with basic education, who least registered requests for information, to the public with higher education. The results also indicate that the absence of educational actions influenced information literacy skills and limited citizen participation, by demonstrating that applicants with higher education had a greater presence in records of information requests, as well as greater success in terms of the information provided. This may be leading many individuals to seek information from unofficial sources, controlled by hegemonic power groups, undermining the construction of critical thinking, and interfering with the real needs experienced.